Pre-treatment of melatonin enhances the seed germination responses and physiological mechanisms of soybean (Glycine max L.) under abiotic stresses - Awan, Samrah Afzal; Khan, Imran; Wang, Qi; Gao, Jing; Tan, Xianming; Yang, Feng (Frontiers in Plant Science, 2023)
The germination of soybean seeds is critically affected by abiotic stresses resulting in decreasing crop growth and yield. However; little is known about the physiological mechanisms of germination and the role of melatonin on soybean seed germination under drought, salt, cold, and heat stresses. Therefore, the current study investigated the potential role of melatonin to enhance germination indices and other physiological attributes by alleviating the harmful impacts of these stresses during germination. Seeds of soybean were pre-treated (seed priming) with melatonin at MT1 (20 μmol L-1), MT2 (50 μmol L-1), MT3 (100 μmol L-1), MT4 (200 μmol L-1), and MT5 (300 μmol L-1) and exposed to these four stresses. It was noted that MT1 (20 μmol L-1), MT2 (50 μmol L-1), and MT3 (100 μmol L-1) remarkably improved the germination potential, germination rate, radical lengths, and biomass under abiotic stresses. Furthermore, MT1, MT2, and MT3 progressively improved the proline to minimize the impact of drought, salt, cold, and heat stresses. In addition, higher oxidative damage in terms of malondialdehyde content (MDA) and hydrogen peroxide H2O2 was noted higher under salt (150 mM NaCl) and heat (30 °C) stresses as compared to drought (PEG 15%) and cold (10 °C) stress. Moreover, MT2 and MT3 significantly enhanced the activities of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) to reduce the oxidative damage in soybean seeds during the germination. Overall, melatonin at 50 μmol L-1 and 100 μmol L-1 considerably mitigated the harmful impacts of drought, salt, cold, and heat stress by enhancing germination and other physiological mechanisms of soybean. This study could provide bases to enhance the melatonin-mediated tolerance of soybean and other related crops at early growth stages when exposed to abiotic stresses.